Resuscitative Endovascular Balloon Occlusion of the Aorta: Review of the Literature and Applications to Veterinary Emergency and Critical Care - Hoareau, Guillaume L.; Tibbits, Emily M.; Beyer, Carl A.; Simon, Meryl A.; DeSoucy, Erik S.; Faulconer, E. Robert; Neff, Lucas P.; Grayson, J. Kevin; Stewart, Ian J.; Williams, Timothy K.; Johnson, M. Austin (Frontiers in Veterinary Science, 2019)
While hemorrhagic shock might be the result of various conditions, hemorrhage control and resuscitation are the corner stone of patient management. Hemorrhage control can prove challenging in both the acute care and surgical settings, especially in the abdomen, where no direct pressure can be applied onto the source of bleeding. Resuscitative endovascular balloon occlusion of the aorta (REBOA) has emerged as a promising replacement to resuscitative thoracotomy (RT) for the management of non-compressible torso hemorrhage in human trauma patients. By inflating a balloon at specific levels (or zones) of the aorta to interrupt blood flow, hemorrhage below the level of the balloon can be controlled. While REBOA allows for hemorrhage control and augmentation of blood pressure cranial to the balloon, it also exposes caudal tissue beds to ischemia and the whole body to reperfusion injury. We aim to introduce the advantages of REBOA while reviewing known limitations. This review outlines a step-by-step approach to REBOA implementation, and discusses common challenges observed both in human patients and during translational large animal studies. Currently accepted and debated indications for REBOA in humans are discussed. Finally, we review possible applications for veterinary patients and how REBOA has the potential to be translated into clinical veterinary practice.